2004
DOI: 10.1016/j.femsle.2004.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of recombinant methylated HBHA inMycobacterium smegmatis

Abstract: The Heparin-Binding Haemagglutinin (HBHA) is a mycobacterial adhesin involved in the dissemination of Mycobacterium tuberculosis from the site of primary infection and a potential candidate for the development of a new vaccine against tuberculosis. Methylation of HBHA is a novel post-translational event that imparts important immunological properties to the protein. Since recombinant HBHA expressed in Escherichia coli is not methylated, we investigated the possibility of producing recombinant methylated HBHA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 23 publications
0
60
1
Order By: Relevance
“…Expression of Rv0805 in M. smegmatis-Rv0805 and its mutants were expressed under the Rv0805 gene promoter in M. smegmatis using derivatives of the pMV-10 -25 plasmid (23). Generation of plasmid constructs for expression of Rv0805, Rv0805N97A, Rv0805⌬40, and Rv0805⌬40N97A have been described earlier (19).…”
Section: Methodsmentioning
confidence: 99%
“…Expression of Rv0805 in M. smegmatis-Rv0805 and its mutants were expressed under the Rv0805 gene promoter in M. smegmatis using derivatives of the pMV-10 -25 plasmid (23). Generation of plasmid constructs for expression of Rv0805, Rv0805N97A, Rv0805⌬40, and Rv0805⌬40N97A have been described earlier (19).…”
Section: Methodsmentioning
confidence: 99%
“…Dose-response experiments revealed that optimum IFN-c secretion occurred at a HBHA dose of 100 mg?mL -1 using peripheral mononuclear cells. Methylated HBHA antigen was produced in cultures of Mycobacterium smegmatis 3.38 as previously described [20]. 4) IFN-c ELISPOT responses to purified protein derivative (PPD; 100 mg?mL -1 ; Staten Serum Institute, Copenhagen, Denmark) were performed using IFN-c pre-coated ELISPOT plates.…”
Section: Methodsmentioning
confidence: 99%
“…1-318 and Rv0805 1-278 coding sequences were amplified as described earlier (6), and cloned into pMV10 -25 (22), to allow expression of Rv0805 under the mycobacterial hsp60 gene promoter. A control vector (pMV vector control) was generated by digesting pMV10 -25 with NheI and XbaI and religating the vector backbone.…”
Section: ϩmentioning
confidence: 99%